1999
DOI: 10.1200/jco.1999.17.8.2604
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and Pharmacokinetic Study of Temozolomide on a Daily-for-5-Days Schedule in Patients With Advanced Solid Malignancies

Abstract: Prior myelosuppressive therapy was not a determinant of toxicity. TMZ 150 mg/m(2)/d administered as a single oral dose daily for 5 days every 4 weeks is well tolerated by MP and HP patients, with higher doses resulting in unacceptably high rates of severe hematologic toxicity. TMZ doses should be individualized according to BSA rather than use of a prespecified oral dose for all individuals. TMZ is an optimal agent to develop in combination with other cytotoxic, biologic, and targeted therapeutics for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 14 publications
4
85
0
1
Order By: Relevance
“…The results of our pharmacokinetic analysis are similar to those observed in studies of adults with advanced solid tumors who received the same temozolomide regimen at doses of 100 -200 mg/m 2 per day. 18 In the current study, the apparent oral clearance of temozolomide was 4.5 L/m 2 per hour, whereas the clearance was 6.9 L/m 2 per hour in adult patients receiving equivalent dosages in the study conducted by Hammond et al 18 . In addition, the mean temozolomide AUC reported in adults was 30 g/mL per hour, compared with 41 g/mL per hour for patients in the current study who were treated at the same dose.…”
Section: Discussionmentioning
confidence: 45%
“…The results of our pharmacokinetic analysis are similar to those observed in studies of adults with advanced solid tumors who received the same temozolomide regimen at doses of 100 -200 mg/m 2 per day. 18 In the current study, the apparent oral clearance of temozolomide was 4.5 L/m 2 per hour, whereas the clearance was 6.9 L/m 2 per hour in adult patients receiving equivalent dosages in the study conducted by Hammond et al 18 . In addition, the mean temozolomide AUC reported in adults was 30 g/mL per hour, compared with 41 g/mL per hour for patients in the current study who were treated at the same dose.…”
Section: Discussionmentioning
confidence: 45%
“…2b). Considering that the median serum concentration measured in patients treated with TMZ at 150 mg/m 2 in clinical settings corresponds to 50 lM (Hammond et al 1999), it becomes clear how this gain in MGMT levels may confer acquired resistance. Depletion of MGMT with O 6 -BG largely restored TMZ sensitivity, although the resistance of LN-18_R remained slightly above that of parental cells, underlining that chemoresistance is multimodal and involves more than one pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The highest dose (250 mg m À2 Â 5) caused grade 3 -4 thrombocytopenia in nine out of 18 patients (50%) vs three out of 50 patients (6%) starting with 200 mg m À2 . Several phase I trials of TMZ in patients with advanced cancer also demonstrated myelosuppression, especially thrombocytopenia, as the DLT (Dhodapkar et al, 1997;Hammond et al, 1999;Newlands et al, 1992;O'Reilly et al, 1993). The thrombocytopenia was always transient and bleeding was not observed.…”
Section: Discussionmentioning
confidence: 99%